1995
DOI: 10.1095/biolreprod52.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Fas Antigen-Mediated Apoptosis in Human Granulosa/luteal Cells1

Abstract: The Fas antigen is a transmembrane receptor that can trigger apoptosis in a variety of tumor and hematopoietic cells. Ovarian follicular atresia and luteolysis are thought to occur by apoptosis. Using reverse transcriptase-polymerase chain reaction (RT-PCR) and flow cytometry, we demonstrated that human granulosa/luteal cells express the Fas antigen. An anti-human Fas antigen monoclonal antibody (Fas mAb; clone CH-11), which induces apoptosis in other cell types by binding to the Fas antigen, induced significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
142
2
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(149 citation statements)
references
References 45 publications
2
142
2
3
Order By: Relevance
“…Many previous reports, including ours, demonstrated expression of Fas on granulosa cells. [31][32][33][34][35][36][37][38] A few reports suggested expression of Fas on oocytes 32,38,39 although we could not detect it. On the other hand, Kit expression was shown to be restricted on oocytes but not on granulosa cells in follicles, 13,18,55 while deficiency of Kit leads to Fas-induced loss of granulosa cells as well as oocytes.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Many previous reports, including ours, demonstrated expression of Fas on granulosa cells. [31][32][33][34][35][36][37][38] A few reports suggested expression of Fas on oocytes 32,38,39 although we could not detect it. On the other hand, Kit expression was shown to be restricted on oocytes but not on granulosa cells in follicles, 13,18,55 while deficiency of Kit leads to Fas-induced loss of granulosa cells as well as oocytes.…”
Section: Discussionmentioning
confidence: 78%
“…28 In female gonads, we and others demonstrated that Fas is expressed on granulosa cells of various follicles and luteal cells. [31][32][33][34][35][36][37][38] A few reports showed Fas expression on oocytes, but we have not been able to confirm this. 32,38,39 The expression on granulosa and luteal cells suggests that Fas is involved in follicular atresia and luteolysis for the gonadal homeostasis of adult mice.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…This result suggests that the amount of bax present in granulosa cells that maintain a constitutive level of bcl-2 expression may be linked to the induction of granulosa cell apoptosis and follicular atresia mediated by heat-stress. It is known that another apoptotic signaling cascade, the Fas/Fas ligand (FasL) system, can lead to granulosa cell apoptosis (Quirk et al 1995, Hakuno et al 1996, Kim et al 1998). Thus, it is possible that heat stress stimulates the Fas/FasL cascade in the granulosa cells of growing follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death ligand and receptor systems [such as the Fas ligand (FasL)/Fas system and TNF relating apoptosis inducing ligand (TRAIL)/TRAIL-receptor system] mediate apoptosis during follicular aresia in porcine ovaries [18][19][20][21][22][23][24][25][26][27]. In porcine granulosa cells, apoptosis is regulated by a cell death ligand and receptor system, TRAIL/TRAIL-R, as follows [22].…”
mentioning
confidence: 99%